2019
DOI: 10.3390/vaccines7040146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pneumococcal Surface Protein A as a Vaccine Antigen against Secondary Streptococcus pneumoniae Challenge during Influenza A Infection

Abstract: Secondary bacterial pneumonia is responsible for significant morbidity and mortality during seasonal and pandemic influenza. Due to the unpredictability of influenza A virus evolution and the time-consuming process of manufacturing strain-specific influenza vaccines, recent efforts have been focused on developing anti-Streptococcus pneumoniae immunity to prevent influenza-related illness and death. Bacterial vaccination to prevent viral-bacterial synergistic interaction during co-infection is a promising conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…These results extend the findings from our previous work, which illustrated that an age-associated decrease in NLRP3 inflammasome activation contributed to increased morbidity and mortality of aged adult mice to secondary S. pneumoniae at day 14 post influenza [52]. Similar to previously published studies in young adult mice, we also observed a dramatic reduction in vaccine efficacy against S. pneumoniae in the presence of influenza [17,30,31]. Based on these results, it is possible that the immune priming response that occurs during influenza can have a direct negative impact on adaptive vaccine responses in aged adult lung.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results extend the findings from our previous work, which illustrated that an age-associated decrease in NLRP3 inflammasome activation contributed to increased morbidity and mortality of aged adult mice to secondary S. pneumoniae at day 14 post influenza [52]. Similar to previously published studies in young adult mice, we also observed a dramatic reduction in vaccine efficacy against S. pneumoniae in the presence of influenza [17,30,31]. Based on these results, it is possible that the immune priming response that occurs during influenza can have a direct negative impact on adaptive vaccine responses in aged adult lung.…”
Section: Discussionsupporting
confidence: 92%
“…As recent work has illustrated differential efficacy of Prevnar vaccination in modulating the immune responses of adult mice to a post-influenza infection with a serotype 3 strain of Streptococcus pneumoniae, we chose to examine the impact of Pneumovax on these responses [30,40]. Given these findings, it would be plausible that other vaccines, designed with specific bacterial components, such as pneumococcal surface protein A (PspA) and pneumolysin (Ply) or liposomal encapsulation of polysaccharides (LEPS), may improve efficacy to post-influenza S. pneumoniae infection [31,[43][44][45]. Future work will need to evaluate if additional vaccine types can prove efficacious and further reduce inflammatory cytokine production while improving bacterial clearance post-influenza infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations